Smart Traffic Light Using YOLO Based Camera with Deep Reinforcement Learning Algorithm - Mochammad Sahal; Zulkifli Hidayat; Yusuf Bilfaqih; Mohamad Abdul Hady; Yosua Marthin Hawila Tampubolon (JAREE (Journal on Advanced Research in Electrical Engineering), 2023)
Congestion is a common problem that often occurs in big cities. Congestion causes a lot of losses, such as in terms of time, economy, to the psychology of road users. One of the causes of congestion is traffic lights that are not adaptive to the dynamics of traffic flow. This final project tries to solve this problem using a Reinforcement Learning approach combined with a SUMO (Simulation of Urban Mobility) traffic simulator. The data used is the real video data of the KD Cowek intersection, Surabaya. The video data is processed using the YOLO algorithm which will detect and count vehicles. The output of the video processing will be used in Reinforcement Learning. The result of Reinforcement Learning is that the total length of the traffic queue at 06.00 – 09.00 has an average of 106 vehicles.